Developing an Online Science Journal Collection: A Quick Tool for Assigning Priorities. - Anne Christie; Laurel L. Kristick (Issues in Science and Technology Librarianship)
Oregon State University Libraries are committed to increasing electronic access to information. The catalog, myriad databases, and a small collection of e-books are accessible over the Internet. OSU Libraries are now focusing attention on access to primary science journals. Using an existing library liaison network, we conducted an informal e-mail poll of science faculty. We asked them for lists of the "top ten" journals that they would like to access electronically. These faculty lists have been compiled into an Excel spreadsheet for analysis. Other data added to the spreadsheet include the publisher, whether or not the Libraries have a current subscription (print or electronic), cost of the subscription, licensing conditions and the ISI impact factors and rankings. We are using this information to set priorities for the allocation of staff time and available funding to develop the online science journal collection.